2004
DOI: 10.2337/diacare.27.10.2306
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study of Diabetes and Its Characteristics During the Fasting Month of Ramadan in 13 Countries

Abstract: OBJECTIVE -The aim of this study was to assess the characteristics and care of patients with diabetes in countries with a sizable Muslim population and to study diabetes features during Ramadan and the effect of fasting.RESEARCH DESIGN AND METHODS -This was a population-based, retrospective, transversal survey conducted in 13 countries. A total of 12,914 patients with diabetes were recruited using a stratified sampling method, and 12,243 were considered for the analysis.RESULTS -Investigators recruited 1,070 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
651
6
42

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 616 publications
(720 citation statements)
references
References 13 publications
21
651
6
42
Order By: Relevance
“…The largest dataset is the recent EPIDIAR study (4), which showed that fasting during Ramadan increased the risk of severe hypoglycemia (defined as hospitalization due to hypoglycemia) some 4.7-fold in patients with type 1 diabetes (from 3 to 14 events ⅐ 100 people Ϫ1 ⅐ month Ϫ1 ) and ϳ7.5-fold in patients with type 2 diabetes (from 0.4 to 3 events ⅐ 100 people Ϫ1 ⅐ month…”
Section: Hypoglycemiamentioning
confidence: 99%
See 1 more Smart Citation
“…The largest dataset is the recent EPIDIAR study (4), which showed that fasting during Ramadan increased the risk of severe hypoglycemia (defined as hospitalization due to hypoglycemia) some 4.7-fold in patients with type 1 diabetes (from 3 to 14 events ⅐ 100 people Ϫ1 ⅐ month Ϫ1 ) and ϳ7.5-fold in patients with type 2 diabetes (from 0.4 to 3 events ⅐ 100 people Ϫ1 ⅐ month…”
Section: Hypoglycemiamentioning
confidence: 99%
“…Due to the limited information available from prospective or retrospective studies on the effects of fasting during Ramadan, a group of endocrinologists and diabetologists from a number of Muslim and non-Muslim countries met to exchange information and opinions and to propose a set of recommendations. Although recommendations for management of diabetes in patients who elect to fast during Ramadan were proposed in 1995 at a conference in Casablanca (5), the present effort was prompted by data from the EPIDIAR study (4) showing that fasting is quite common among Muslims with diabetes and by the increasing awareness that this represents a global medical issue. The purposes of the recommendations that follow are threefold: 1) to invite an open dialogue on this important topic, 2) to offer a set of medical opinions and suggestions, and 3) to identify topics of research needed to answer important medical questions regarding fasting during Ramadan.…”
mentioning
confidence: 99%
“…Long periods of fasting and drastic changes in food and water intake increase the risk of hypoglycaemia, hyperglycaemia, and dehydration in these individuals. Patients with T2DM who fast during Ramadan have a 7.5‐fold increased risk of severe hypoglycaemia during Ramadan compared with non‐fasting months 2. Generally, insulin‐independent treatments for T2DM are associated with a lower risk of hypoglycaemia than treatments that increase insulin secretion,3 so these treatments may be more attractive options for patients who intend to fast during Ramadan, or at other times throughout the year.…”
Section: Introductionmentioning
confidence: 99%
“…nessuno studio è stato condotto sull'influenza che episodi di iperglicemia ripetuti in un periodo ristretto di 4 settimane possano avere sullo sviluppo o sulla progressione delle complicanze [11]. Certamente lo studio EPIDIAR [9] ha dimostrato il significativo incremento di iperglicemie gravi con o senza chetoacidosi, con necessità di ricovero, durante il Ramadan, nella misura di 1:5 per il diabete di tipo 1 e di 1:3 per il diabete di tipo 2. Le cause sono da ricercare nell'incremento della glicogenolisi e della gluconeogenesi, nella riduzione non controllata del trattamento farmacologico, giustificata da una riduzione dell'introito alimentare e nel cattivo controllo metabolico nel periodo precedente il Ramadan.…”
Section: Rischi Associati Al Digiunounclassified